Imperial legacies and southern penal spaces: A study of hunting nomads in postcolonial India - Brown, Mark (Punishment & society, 2021)
Southern penal spaces are marked by resemblances and affinities with colonial regimes of control, yet they also reflect quite distinctive postcolonial social and political dynamics found in the global south. Here, legacies of control, forms of exile, status reductions, hierarchical social stratifications and other like forms come together in robust modes of containment suitable for managing ‘marginal’ and ‘suspect’ populations. We draw on ethnographic empirical work with two hunting nomadic groups in India by two of the co-authors who are working with the Kheria Sabar community in Purulia district in West Bengal and Pardhi community in Mumbai. The latter were subject to notification under the notorious Criminal Tribes Act 1871, marking them out as ‘criminal tribes’ until their de-notification shortly after India's independence in 1947, yet the Kheria Sabars too feel its effects. We draw attention here to the continual negotiation and (re)fabrication of both state and citizen at the point of their everyday contact. Our notion of southern penal spaces contributes to penal theory by breaking from northern societies’ focus on institutional carcerality and capturing instead both the variety and the dispersal of penal and punitive practices found in postcolonial societies of the south.